Unlocking the Potential of Greater Female Employment in Europe - Lone Christiansen; Huidan Lin; Joana Pereira; Petia Topalova; Rima Turk (Intereconomics, 2017)
This paper investigates the drivers of female labour force participation in Europe, as well as the implications of achieving greater gender diversity in senior corporate positions. Re-examining the drivers of women's decisions to work is particularly important in the context of Europe. In many European countries, the process of closing gender gaps in labour force participation has stalled, despite greater gender equality in human capital investment, declining birth rates, changing social norms and equal legal access to employment opportunities.
Keywords: 330